Gut microbiota in relationship to diabetes mellitus and its late complications with a focus on diabetic foot syndrome: A review - Sechovcová, Hana; Mahayri, Tiziana Maria; Mrázek, Jakub; Jarošíková, Radka; Husáková, Jitka; Wosková, Veronika; Fejfarová, Vladimíra (Folia microbiologica, 2024)
Diabetes mellitus is a chronic disease affecting glucose metabolism. The pathophysiological reactions underpinning the disease can lead to the development of late diabetes complications. The gut microbiota plays important roles in weight regulation and the maintenance of a healthy digestive system. Obesity, diabetes mellitus, diabetic retinopathy, diabetic nephropathy and diabetic neuropathy are all associated with a microbial imbalance in the gut. Modern technical equipment and advanced diagnostic procedures, including xmolecular methods, are commonly used to detect both quantitative and qualitative changes in the gut microbiota. This review summarises collective knowledge on the role of the gut microbiota in both types of diabetes mellitus and their late complications, with a particular focus on diabetic foot syndrome.
Keywords: Diabetic Foot; Obesity; diabetes mellitus; Diabetes Mellitus; lidé; Diabetic Retinopathy; diabetické nefropatie; diabetická noha; obezita; Diabetic Nephropathies; diabetická retinopatie; střevní mikroflóra; Gastrointestinal Microbiome; Humans